Formation Timescales of Amorphous Rims on Lunar Grains Derived From ARTEMIS Observations. Issue 1 (9th January 2018) - Poppe, A. R.; Farrell, W. M.; Halekas, J. S.
Abstract: The weathering of airless bodies exposed to space is a fundamental process in the formation and evolution of planetary surfaces. At the Moon, space weathering induces a variety of physical, chemical, and optical changes including the formation of nanometer‐sized amorphous rims on individual lunar grains. These rims are formed by vapor redeposition from micrometeoroid impacts and ion irradiation‐induced amorphization of the crystalline matrix. For ion irradiation‐induced rims, however, laboratory experiments of the depth and formation timescales of these rims stand in stark disagreement with observations of lunar soil grains. We use observations by the Acceleration, Reconnection, Turbulence, and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS) spacecraft in orbit around the Moon to compute the mean ion flux to the lunar surface between 10 eV and 5 MeV and convolve this flux with ion irradiation‐induced vacancy production rates as a function of depth calculated using the Stopping Range of Ions in Matter model. By combining these results with laboratory measurements of the critical fluence for charged‐particle amorphization in olivine, we can predict the formation timescale of amorphous rims as a function of depth in olivinic grains. This analysis resolves two outstanding issues: (1) the provenance of >100 nm amorphous rims on lunar grains and (2) the nature of the depth‐age relationship for amorphous rims on lunar grains. Key Points: We have calculated the mean ion flux to the Moon from 10 eV to 5 MeV using 5 years of ARTEMIS observations The mean ion spectrum at the Moon induces rim formation on lunar grains at depths up to and exceeding 500 nm Analysis explains the presence of anomalously thick grain rims and predicts their relationship with formation times